Asymptomatic carriers of the p.A53T SNCA mutation: Data from the PPMI study. (May 2022) - Simitsi, Athina Maria; Koros, Christos; Stamelou, Maria; Beratis, Ion; Efthymiopoulou, Efthymia; Papadimitriou, Dimitra; Bougea, Anastasia; Picillo, Marina; Stanitsa, Evangelia; Papagiannakis, Nikolaos; Antonelou, Roubina; Pachi, Ioanna; et al.
Abstract: We assessed non motor characteristics of 12 asymptomatic p.A53T mutation carriers (A53T-AC) compared with 36 healthy controls (HC) enrolled in the Parkinson's Progression Markers Initiative (PPMI) study. Olfaction score was lower and anxiety was marginally more prevalent in A53T- AC. These findings suggest distinct prodromal features in this group of subjects. Highlights: Olfactory function is more affected in A53T-AC compared to HC. We found a strong positive correlation between UPSIT score and MOCA in A53T-AC but not in HC. Anxiety was more prevalent in A53T-AC.